Early Efficacy of Type I Collagen-Based Matrix-Assisted Autologous Chondrocyte Transplantation for the Treatment of Articular Cartilage Lesions - Li, Xiang; Li, Shiao; Qian, Jiatian; Chen, Yancheng; Zhou, Yiqin; Fu, Peiliang (Frontiers in Bioengineering and Biotechnology, 2021)
Background: Articular cartilage is a complex structure that allows for low frictional gliding and effective shock absorption. Various sports injuries and inflammatory conditions can lead to lesions in the articular cartilage, which has limited regenerative potential. Type I collagen combined with autologous chondrocytes in a three-dimensional culture were used to induce the regeneration of single-layer autologous expanded chondrocytes without chondrogenic differentiation. Purpose: To assess the clinical, radiological, and histological changes following collagen-based autologous chondrocyte transplantation (MACT) for chondral knee lesions. Methods: The study prospectively enrolled 20 patients with symptomatic knee chondral lesions (mean size defect was 2.41±0.43 cm2, range: 2.0 to 3.4 cm2) in the lateral femoral condyle and femoral groove who underwent type I collagen-based MACT between July 2017 and July 2019. KOOS was assessed before the procedure, and periodic clinical follow-up was conducted every three months for a maximum of 12 months following the procedure and at one-year intervals thereafter. MRI T2 mapping of repaired cartilage was also used for the quantitative analysis of regeneration. In one patient, second-look arthroscopy was performed to assess cartilage regeneration characteristics, and a portion of regenerated cartilage was harvested for histological evaluation 12 months after implantation. Results: At pre-operation and at three, six, 12, and 24 months after the operation, KOOS pain, symptoms, daily life activities, sports and recreation, as well as the quality of life were significantly improved between every two time points. HE staining indicated that the newly formed cartilage was comprised of naive chondrocytes. Safranin O-fast green staining of the regenerated tissue revealed fibroblast-like cells surrounded by glycosaminoglycans. Immunohistochemistry analysis indicated that the expression of collagen type II was greater and more evenly distributed than that of collagen type I. The T2 values for repaired tissue gradually decreased, eventually approaching near-average values. Conclusion: The present study demonstrated that type I collagen-based MACT is a clinically effective treatment. Histological evidence confirmed hyaline cartilage induction. The quantitative MRI T2 mapping test indicated that there still was a difference between the transplanted cartilage and the surrounding hyaline cartilage. Taken together, the current method represents an efficient approach for cartilage lesions.